Association between anger rumination and autism symptom severity, depression symptoms, aggression, and general dysregulation in adolescents with autism spectrum disorder. (February 2017) - Patel, Shivani; Day, Taylor N; Jones, Neil; Mazefsky, Carla A
Rumination has a large direct effect on psychopathology but has received relatively little attention in autism spectrum disorder despite the propensity to perseverate in this population. This study provided initial evidence that adolescents with autism spectrum disorder self-report more anger-focused rumination than typically developing controls, though there was substantial within-group variability. Anger rumination was positively correlated with autism symptom severity with both groups combined. Future studies that include measures of perseveration on special interests are needed to understand whether anger rumination is a manifestation of a perseverative type of repetitive behavior or a distinct trait. Even when controlling for autism symptom severity, however, anger-focused rumination was associated with poorer functioning, including more depression symptoms and overall emotional and behavioral dysregulation. Therefore, further inquiry regarding anger rumination in autism spectrum disorder is clinically important, and the potential impact of rumination-focused interventions should be explored.